Rational Design of Peptide-based Smart Hydrogels for Therapeutic Applications - Das, Saurav; Das, Debapratim (Frontiers in Chemistry, 2021)
Peptide-based hydrogels have captivated remarkable attention in recent times and serve as an excellent platform for biomedical applications owing to the impressive amalgamation of unique properties such as biocompatibility, biodegradability, easily tunable hydrophilicity/hydrophobicity, modular incorporation of stimuli sensitivity and other functionalities, adjustable mechanical stiffness/rigidity and close mimicry to biological molecules. Putting all these on the same plate offers smart soft materials that can be used for tissue engineering, drug delivery, 3D bioprinting, wound healing to name a few. A plethora of work has been accomplished and a significant progress has been realized using these peptide-based theranostics. However, designing hydrogelators with the desired functionalities and their self-assembled nanostructures is still highly serendipitous in nature and thus a roadmap providing guidelines toward designing and preparing these soft-materials and applying them for a desired goal is a pressing need of the hour. This review aims to provide a concise outline for that purpose and the design principles of peptide-based hydrogels along with their potential for biomedical applications are discussed with the help of selected recent reports.